Fire behavior of shallow prestressed hollow core slabs from computational modeling - ARAÚJO,D. L. (2020)
Abstract Prestressed hollow core slabs are one of the structural systems whose use has increased the most in recent years in Brazil due to its efficiency and versatility. They can be used in many types of structural systems, such as masonry, precast concrete, cast-in-place concrete and steel structures. However, there are few analytical models to evaluate the fire behavior of hollow core slabs. In a simplified way, the fire resistance is evaluated indirectly through the minimum distance of the surface in contact with fire to the reinforcement axis. In this paper, some numerical models in finite element software were developed to analyze the variation of temperature with ﬁre exposure time of shallow hollow core slabs, focusing on the presence of voids in the transversal section of the slab. The 500 °C isotherm method applied to 20 cm high slabs confirmed the Standard Fire Resistance obtained from the tabular method. However, when applied to shallow prestressed hollow core slabs that are 16 cm high, the 500 °C isotherm method indicated that the Standard Fire Resistance of these slabs is lower than values obtained from tabular methods.